38. Is the answer. Go go go!
Answer:
(C) f’(c) = 0 and f”(c) > 0
Step-by-step explanation:
A minimum occurs where the first derivative is 0 (the tangent line is horizontal), and the second derivative is positive (concave up). The simplest example of this is a positive parabola, like y = x², which has a relative minimum at its vertex.
Answer:
MAMMAAAAAAA OOOooOOOoooOOO
Step-by-step explanation:
M A M M A A A A A A A O O O o o O O O o o o O O O
Answer:
![(x^{-3} )^{2}](https://tex.z-dn.net/?f=%28x%5E%7B-3%7D%20%29%5E%7B2%7D)
![x^6 x^{-12}](https://tex.z-dn.net/?f=x%5E6%20x%5E%7B-12%7D)
Step-by-step explanation:
is the expression given to be solved.
First of all let us have a look at <u>3 formulas</u>:
![1.\ p^a \times p^b = p^{(a+b)}\\2.\ (p^a \times q^b)^c = (p^{a})^c \times (q^{b})^c\\3.\ (p^a)^b = p^{a\times b}](https://tex.z-dn.net/?f=1.%5C%20p%5Ea%20%5Ctimes%20p%5Eb%20%3D%20p%5E%7B%28a%2Bb%29%7D%5C%5C2.%5C%20%28p%5Ea%20%5Ctimes%20q%5Eb%29%5Ec%20%3D%20%28p%5E%7Ba%7D%29%5Ec%20%5Ctimes%20%28q%5E%7Bb%7D%29%5Ec%5C%5C3.%5C%20%28p%5Ea%29%5Eb%20%3D%20p%5E%7Ba%5Ctimes%20b%7D)
Both the formula can be applied to the expression(
) during the first step while solving it.
<u>Applying formula (1):</u>
Comparing the terms of
with ![p^a \times p^b](https://tex.z-dn.net/?f=p%5Ea%20%5Ctimes%20p%5Eb)
![p=x, a =3, b=-6](https://tex.z-dn.net/?f=p%3Dx%2C%20a%20%3D3%2C%20b%3D-6)
So,
is reduced to ![(x^{-3} )^{2}](https://tex.z-dn.net/?f=%28x%5E%7B-3%7D%20%29%5E%7B2%7D)
<u>Applying formula (2):</u>
Comparing the terms of
with ![(p^a \times q^b)^c](https://tex.z-dn.net/?f=%28p%5Ea%20%5Ctimes%20q%5Eb%29%5Ec)
![p=q=x, a =3, b=-6, c=2](https://tex.z-dn.net/?f=p%3Dq%3Dx%2C%20a%20%3D3%2C%20b%3D-6%2C%20c%3D2)
So,
is reduced to
.
So, the answers can be:
![(x^{-3} )^{2}](https://tex.z-dn.net/?f=%28x%5E%7B-3%7D%20%29%5E%7B2%7D)
![x^6 x^{-12}](https://tex.z-dn.net/?f=x%5E6%20x%5E%7B-12%7D)
Good morning☕️
______
Answer:
w is the width
L is the length
p is the perimeter
w=9
L=27
___________________
Step-by-step explanation:
p=2[(L-4) + (w+1)]
⇔p=2[(3w-4) + (w+1)]
⇔p=2[4w-3]
⇔p=8w-6
⇔66=8w-6
⇔8w=72
⇔w=9
Then L=3w=27
:)